A quantitative study of immunoglobulin containing cells in the differential diagnosis of acute colitis. - van Spreeuwel, J P (1985)
In colonic biopsies of 33 patients with acute colitis caused by campylobacter, salmonella, or shigella immunoglobulin containing cells were determined quantitatively using an indirect immunoperoxidase technique and morphometry with a graphic tablet. The findings were compared with those of 10 patients without histological abnormalities, 10 patients with Crohn's disease of the colon, and 10 patients with ulcerative colitis. Biopsies of patients with acute infectious colitis had increased numbers of IgA containing cells and to a lesser extent IgM containing cells but not IgG containing cells compared with controls. Compared with the patients with active chronic idiopathic inflammatory bowel disease the patients with acute colitis showed significantly lower relative and absolute numbers of IgG containing cells. We therefore conclude that quantitative assessment of immunoglobulin containing cells in colonic biopsies may be useful in the differential diagnosis of acute infectious colitis and chronic idiopathic inflammatory bowel disease.